Development and validation of the Leadership Effectiveness in Africa and the Diaspora (LEAD) scale. (December 2020) - Michaud, James; Lvina, Elena; Galperin, Bella L; Lituchy, Terri R; Punnett, Betty Jane; Taleb, Ali; Mukanzi, Clive; Senaji, Thomas; Bagire, Vincent; Puplampu, Bill; Ford, David L; Acquaah, Moses; et al.
This article contributes to the literature on cross-cultural leadership by describing the development and validation of the Leadership Effectiveness in Africa and the Diaspora (LEAD) Scale. The LEAD Scale is a culturally sensitive measure of leadership effectiveness in the understudied settings of Africa and the African diaspora. A combination of methods and four studies using samples from Africa and the African diaspora based in Canada, the USA, and the Caribbean were used to develop the measure. Using the grounded theory approach and the Delphi technique ( n = 192), followed by a set of increasingly rigorous tests including exploratory factor analysis ( n = 441), confirmatory factor analysis ( n = 116), and a test of measure invariance ( n =1384), we developed and validated a culturally sensitive measure of effective leadership. Our results demonstrate that spirituality, tradition and community-centredness are important and culturally specific components of leadership in Africa and the African diaspora. This paper provides a validated measure of leadership and offers recommendations regarding the use of the measure by managers and researchers working in Africa or with African diaspora.